2017
DOI: 10.1177/0972262917716760
|View full text |Cite
|
Sign up to set email alerts
|

FX Volatility Impact on Indian Stock Market: An Empirical Investigation

Abstract: Examining the interrelationship between currency market volatility and stock market volatility will create abundant trading opportunities to the investors irrespective of whether the return of one market is moving up or down. This research work intended to examine how the exchange rate volatility between Indian rupee and foreign currencies, such as US dollar, euro, Japanese yen and British pound, can influence the return and volatility of the Indian stock market. The research data extensively cover daily price… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 24 publications
(23 reference statements)
5
11
0
Order By: Relevance
“…Moreover, the conducted research confirmed the interrelationship between a currency market volatility and a stock market volatility, and that the volatility shocks between the stock market and currency market are quite persistent (Aravind, 2017).…”
Section: Stock Vs Forex Tradingsupporting
confidence: 66%
“…Moreover, the conducted research confirmed the interrelationship between a currency market volatility and a stock market volatility, and that the volatility shocks between the stock market and currency market are quite persistent (Aravind, 2017).…”
Section: Stock Vs Forex Tradingsupporting
confidence: 66%
“…The relationship between stock market return, price movements, and forex price variations http://dx.doi.org/10.21511/imfi.19 (4).2022.06 has been widely explored (Patel, 2017). Aravind (2017) analyzed the effect of volatility in Forex rates of the Indian rupee with other major global currencies like US Dollar, Euro, Japanese Yen, and GBP on the stock price and return volatility in the Indian stock market using the granger causality test. The study exhibited a weak causal relationship between the exchange rate of USD, EUR and JPY to stock returns but a positive relationship with GBP.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The numerous existing studies dealing with the volatility of the Indian foreign exchange market such as Sahoo et al (2017), Zabiulla (2015) and Aravind (2017), to name a few, are based on the volatility of the underlying dollar–rupee exchange rate returns. These studies typically measure dollar-rupee volatility using an econometric model from the GARCH family.…”
Section: Literature Reviewmentioning
confidence: 99%